Hailstorms in the High Plains - Schleusener, Richard A., author; Auer, August H., author; Colorado State University, Civil Engineering Section, publisher (Colorado State University. Libraries, 1964)
The instrumentation and data collection system used in hailstorm studies in northeastern Colorado for the period 1960 through 1964 is d e scribed. Basic data were derived from cooperative observers and passive hailfall indicators to obtain information on rainfall and hailfall to supplement the existing stations. Systematic efforts were made through news letters to inform people in the area of the research work being conducted. In 1964, assistance was given by the Colorado State Highway Patrol in reporting rainfalls and hailfalls, which proved to be particularly valuable in establishing negative reports of hail falls. A variety of radar equipment was used to establish radar characteristics of hailstorms. Cloud seeding on selected thunderstorms was done with silver iodide generators in 1962 and 1963 in limited cases. These results are reported separately. The main body of the report gives a summary of project reports in abbreviated form, and detailed results are given in separate appendices. The reported results are those of a background nature on the characteristics of hailstorms and rainstorms, and the associated physical studies that have been made in the period 1960 through 1963 for the purpose of establishing the necessary background information for a scientific hail suppression experiment to be conducted in northeastern Colorado. The data obtained indicate that such an experiment cannot be conducted on the basis of target and control areas, but must be conducted by studies of the changes in hailstorms as a function of time during their lifetime. Additional physical studies are continuing, as well as continuation of the hail suppression experiment, which was begun in 1964. A detailed report of the results of seeding of individual thunderstorms is being prepared as a separate report.
CER64RAS36.
December 1964.
Final report, NSF Grant G-23706, research supported by the Atmospheric Science Program, National Science Foundation, with supplemental support of Crop-Hail Insurance Actuarial Association.
Keywords: Hail